Clinicopathological Profile, Treatment Response and Survival of Cervical Cancer Patients from a Tertiary Cancer Centre in North Karnataka - Shivamurthy, Sandeep K.; Lethika, Rahul D.; Madabhavi, Irappa V. (Asian Pacific Journal of Cancer Care, 2022)
Background: North Karnataka consisting of large rural population doesnot have any report on carcinoma cervix clinical profile and treatment outcomes. Objectives: analysing the clinicopathological profile and survival data from a tertiary cancer Centre in north Karnataka and comparing it with that of data published worldwide. Methods: We analysed carcinoma cervix patients from our centre between Oct 2014 to Oct 2016. The clinicopathological, treatment-related parameters, outcomes were analysed. Results: A total of 360/450 patients treated radically, 60% of the patients were between 40-60 years with the youngest being 22 years and the eldest 84 years. 33.3% of patients had Comorbidity, 85% patients had History of bleeding. 87%were from rural area, 44.8% were literate. 46.6% of patients had stage IIIB followed by II (27.8%), 3.8%had para-aortic node and 3.1% had pelvic nodes. 93.3% had SCC, 80% received chemoradiation, 13%received adjuvant Radiation/chemoradiation and 7% only surgery. Response data available for 320 patients (88.8%) among 320, 74.6% had complete response, Residual disease present in 14%, 3% patients had stable disease and progressive disease in 7%. At 18 months post-treatment, the survival data were available for only 244 (67.7%) patients, out of which 187 patients (67.7%) were alive. Overall 50% of the patients lost to follow up within 3 years of treatment completion. The 3-year survival for the patients who followed up until 3 years was 62.3% (111/178 patients). The stage-wise 3-year survival was 70.6% for stage I, 83.6% for II, 60% for IIIA, 49% for IIIB, 33.3% for IIIC2 (para-aortic nodal involvement) and 28.6% for stage IVA (P-0.001). Conclusion: Awareness about carcinoma cervix in the rural population is still lacking and they are presenting at an advanced stage, which largely effects on survival of the patients.